2021
DOI: 10.1177/23259671211000038
|View full text |Cite
|
Sign up to set email alerts
|

Association of Ligamentous Laxity, Male Sex, Chronicity, Meniscal Injury, and Posterior Tibial Slope With a High-Grade Preoperative Pivot Shift: A Post Hoc Analysis of the STABILITY Study

Abstract: Background: A spectrum of anterolateral rotatory laxity exists in anterior cruciate ligament (ACL)–injured knees. Understanding of the factors contributing to a high-grade pivot shift continues to be refined. Purpose: To investigate factors associated with a high-grade preoperative pivot shift and to evaluate the relationship between this condition and baseline patient-reported outcome measures (PROMs). Study Design: Cross-sectional study; Level of evidence, 3. Methods: A post hoc analysis was performed of 618… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…Clinical research studies have shown conflicting results. Several studies have shown an association between knee hyperextension and preoperative instability, 4 , 43 postoperative instability, 56 and graft failure, 8 while others report no relationship between hyperextension and risk of laxity or rupture. 7 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical research studies have shown conflicting results. Several studies have shown an association between knee hyperextension and preoperative instability, 4 , 43 postoperative instability, 56 and graft failure, 8 while others report no relationship between hyperextension and risk of laxity or rupture. 7 …”
Section: Discussionmentioning
confidence: 99%
“…Clinical research studies have shown conflicting results. Several studies have shown an association between knee hyperextension and preoperative instability, 4,43 postoperative instability, 56 and graft failure, 8 while others report no relationship between hyperextension and risk of laxity or rupture. 7 High-grade preoperative knee laxity, as determined by a grade 3 Lachman or pivot-shift test result, was significantly associated with 3-times greater odds of graft rupture within the Stability 1 Study, although it was not retained in the asymmetric pivot-shift model.…”
Section: Discussionmentioning
confidence: 99%
“…A steeper tibial slope was significantly correlated with an increase in axial displacement [ 15 17 ] and with the risk of ACL injury [ 15 17 ]. Interestingly, in this study, only a significant increase in tibial slope was found in the noncontact ACL injury group compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Yasuma et al also reported an increased knee rotatory laxity in six fresh-frozen cadavers in the presence of anterolateral structure tears [23]. On the other hand, other authors [24][25][26][27][28][29] that compared the effect of an isolated ALL and iliotibial band resection in an ACL-intact knee did not report significant correlations with tibiofemoral compartment subluxation during a simulated pivot-shift, thus suggesting that the ALL does not represent a primary restraint to the pivot-shift test. The heterogeneous results might be due to the different setups adopted, the age of the specimens and relative quality of the knee structures, and the instrumented device used for the quantitative assessment.…”
Section: Biomed Research Internationalmentioning
confidence: 99%